Penanda Aspek Leksikal dan Aspek Gramatikal Pada Wacana Narasi Di Koran Kompas Edisi Januari-Februari 2016 Serta Wujud Implementasinya Dalam Pembelajaran - Erlinda, Septika Niken, Dra. Atiqa Sabardila, M.Hum (2016)
This study aims to (1) describe the analysis of lexical and grammatical aspects of the narrative discourse in the newspaper Kompas January-February 2016. (2) Describe the implementation in the form of learning. This type of research to examine this problem is the method kualitattif descriptive. A research technique used is the technique literature and technical notes. Presentation techniques using data analysis techniques and techniques pilah decisive element fixed ratio. Results of the study were first discovered, lexical and grammatical aspect markers were discovered data. First, the designation (reference) include this reference persona, demonstrative, and that the reference comparative, the second substitution (substitution) include substitution clause and verbal, third deletion (ellipsis) and assembly (conjunction) contained in the g rammatical aspect. Then the findings of the first lexical aspects, reiterasi (repetition) collocation (collocation). Based on the findings of the aspect of lexical and grammatical then implemented by way of linking these aspects with KI and KD is in school learning. In this case is associated with a high school grade VII KD 4.3 by focusing on descriptive text, a descriptive essay therein appear like this reference (reference), repetitions (reps) were included in the lexical aspects. Therefore, in this study can be used as teaching materials to support the creation of students who have a high potential.